UNSUR-UNSUR INTRINSIK DALAM NOVEL AR-RAJULUL-LAZI AMANA KARYA NAJIB AL-KAILANI: ANALISIS STRUKTURAL ROBERT STANTON - , ZAHROTUN NAIMAH; , Mahmudah, S.S, M.Hum., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Novel ar-Rajulul-lai Amana was a novel written by Egyptian writer, Najib al-Kailani. This Novel recounted the discovery of new belief of a young musician, Iryan Carlo, after such a long time feeling saturated with his social life in his homeland, Italy. He found his new belief without realising it, while he was holding a music concert in Dubai. After he held his new belief, he felt a peace and happiness that he wanted much long time before. The Christian belief that he had long time ago, has finally left by him to embrace a new belief, Islam. The research that will hold on this novel is by using the theory of Robert Stantonâs structural-analysis. As for its method is by using a method of structural analysis, which is by examining and presenting a thorough, and as deep as possible linkages between all of the elements. The intrinsic elements from this novel consisted of the theme, fact stories (characters, plot, and setting), and literary devices (the title and the author's point of view). These elements are identified and described so that it can be determined the connection among lots of different elements into one unified meaning. The results of this research showed that a character in the novel ar-Rajululla i Amana consisted of one developed main character and nine additional characters who did not develop. The Novel used a straight plot through five stages, which are creating situation, generating circumstances, rising action, going into climax, and doing completion phase. This story was set in Rome and Dubai which were representing two contradictory civilizations. The theme of this novel was Islam as a way of life leading man into an eternal happiness. This novel was told in the omniscient point of view. The title of this novel, ar-Rajulul-lai Amana, referred to the main character. Each of these related elements would gain one whole meaning.